2009
DOI: 10.1200/jco.2009.22.4295
|View full text |Cite
|
Sign up to set email alerts
|

KRAS and BRAF Mutations in Advanced Colorectal Cancer Are Associated With Poor Prognosis but Do Not Preclude Benefit From Oxaliplatin or Irinotecan: Results From the MRC FOCUS Trial

Abstract: KRAS/BRAF mutation is associated with poor prognosis but is not a predictive biomarker for irinotecan or oxaliplatin. There is no evidence that patients with KRAS/BRAF mutated tumors are less likely to benefit from these standard chemotherapy agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
378
6
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(419 citation statements)
references
References 38 publications
24
378
6
11
Order By: Relevance
“…RAS mutations represent the only, molecular, predictive biomarker approved for clinical use, while their prognostic role is still debated. Several randomized studies have shown no significant survival differences between KRAS mutated and KRAS wild-type, CRC patients, independently of anti-EGFR therapy (Price et al, 2011;Hecht et al, 2009;Kastrinakis et al, 1995;Russo et al, 1998;Tol et al, 2010), while others have demonstrated a prognostic role of KRAS in advanced disease (Richman et al, 2009;Maughan et al, 2011;Tejpar et al, 2012). BRAF mutations have been described in about 10% of primary CRC, representing a well-known negative prognostic factor, associated with worse survival outcomes, regardless of any treatment received (Ahn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…RAS mutations represent the only, molecular, predictive biomarker approved for clinical use, while their prognostic role is still debated. Several randomized studies have shown no significant survival differences between KRAS mutated and KRAS wild-type, CRC patients, independently of anti-EGFR therapy (Price et al, 2011;Hecht et al, 2009;Kastrinakis et al, 1995;Russo et al, 1998;Tol et al, 2010), while others have demonstrated a prognostic role of KRAS in advanced disease (Richman et al, 2009;Maughan et al, 2011;Tejpar et al, 2012). BRAF mutations have been described in about 10% of primary CRC, representing a well-known negative prognostic factor, associated with worse survival outcomes, regardless of any treatment received (Ahn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7,10,11 The overwhelming majority of KRAS mutations (90%) occur in codons 12 and 13 of exon 2, with the most frequent alteration being a G4A transition in codon 12. 12 The clinical significance of KRAS mutation in colorectal carcinoma patients is controversial; some studies reported no association with survival, 13,14 whereas others suggested that patients with KRASmutated colorectal carcinoma have poorer outcome for any mutation subtype, 15 mutation in codon 12 only 16,17 or codon 13 only. 11 There is more definitive evidence for a negative predictive value of KRAS mutation in patients with advanced stage disease treated with targeted anti-EGFR monoclonal antibody drugs.…”
mentioning
confidence: 99%
“…In CRC, the incidence of KRAS mutations has been reported to be 40% and that of BRAF mutations 5%-10% (Bokemeyer et al, 2009;Richman et al, 2009). However, these data were mainly derived from studies of patient populations in Western countries.…”
mentioning
confidence: 99%